A medicine of constitutions: Sasang medicine in contemporary South Korea - Kim, H (2021)
This thesis investigates the process of standardisation, scientisation, and diversification of Sasang medicine in contemporary South Korea, through the lens of its central concept ch’ejil (constitution 體質). Sasang medicine (sasang ŭihak 四象醫學) is a current of medical tradition which emerged from the scholarly physician Yi Chema (李濟馬) in late 19th century Chosŏn. Sasang medicine is known as ch'ejil ŭihak (constitutional medicine 體質醫學) because it assumes that human beings have different constitutions with different physiologies and pathologies as well as different psychological traits. Sasang medicine is a unique example in [traditional] Korean medicine because it has constantly been practiced for over a century and is ingrained into health practices of modern Koreans as well as the contemporary health care system in South Korea.